2019
DOI: 10.1016/j.solener.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Germanium photovoltaic cells with MoOx hole-selective contacts

Abstract: A. Alcañiz (a) , G. López (a) , I. Martín (a) , A. Jiménez (b) , A. Datas (a,b) , E. Calle (a) , E. Ros (a) , L.G. Gerling (a) , C. Voz (a) , C. del Cañizo (b) , R. Alcubilla (a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
(23 reference statements)
1
16
0
Order By: Relevance
“…[418] , [419] , [420] , [421] , [422] , [423] ), crystalline germanium solar cells (c-Ge) (see e.g. [424] ) and singlecrystal III-V (see e.g. InP [425] ).…”
Section: Wide Bandgap Ferroelectric Oxide Thin-filmsmentioning
confidence: 99%
“…[418] , [419] , [420] , [421] , [422] , [423] ), crystalline germanium solar cells (c-Ge) (see e.g. [424] ) and singlecrystal III-V (see e.g. InP [425] ).…”
Section: Wide Bandgap Ferroelectric Oxide Thin-filmsmentioning
confidence: 99%
“…Although carrier-selective contacts have already been extensively applied in solar cells such as Si, GaAs and InP cells [20][21][22][23], this topic of research is only at its infancy for TPV cells. Alcañiz et al [24] firstly demonstrated a hole selective contact made of transparent substoichiometric molybdenum oxide (MoOx, x<3) on an n-type Ge TPV cell.…”
Section: Thermophotovoltaic (Tpv) Technique Can Directly Convert Infr...mentioning
confidence: 99%
“…Quan et al [9] proposed a noncontact, fast and effective defect detection method for photovoltaic cells that uses a combination of image processing and compressive sensing techniques. Alcañiz et al [10] reported a heterojunction MoOx/Ge PV cell that effectively demonstrates the possibility of creating hole selective contacts in n-type c-Ge. Shittu et al [11] presented the concepts of photovoltaics and thermoelectric energy conversion, research focus areas in the hybrid systems, applications of such systems, discussion of the most recent research accomplishments and recommendations for future research.…”
Section: B-double Exponential Model (Dem)mentioning
confidence: 99%